Do Indigenous American Peoples’ Stories Inform the Study of Dog Domestication? - Mech, L. David (Ethnobiology Letters, 2019)
I discuss the article “Relationships Between Indigenous American Peoples and Wolves 1: Wolves as Teachers and Guides” (Fogg et al. 2015) and the book “The First Domestication: How Wolves and Humans Coevolved” (Pierotti and Fogg 2017). The article proposed that published stories about interactions between indigenous American peoples and wolves (Canis lupus) provide insight into wolf-human relationships as humans began domesticating wolves. In the book, the authors offer a theory of how wolves and humans coevolved by building on the information in the article and the authors’ long experience with captive and pet wolves, wolf-dog hybrids, and dogs. I (1) present arguments and evidence that question the value of indigenous American stories for drawing conclusions about the relationship between early humans and wolves 14,000 yrs BP; (2) demonstrate how indigenous American stories contradict documented information about wolf biology, behavior, and known interactions with humans; and (3) point out important information not considered by the authors about wolf attacks on humans and the importance of rabies in the wolf-human relationship.